'The missing picture': tobacco use through the eyes of smokers. Issue 3 (25th May 2010) - Haines, Rebecca J; Oliffe, John L; Bottorff, Joan L; Poland, Blake D
Abstract : Background: The use of visual methodologies has gained increased prominence among health researchers working with socially marginalised populations, including those studying tobacco and other types of substance use. Objectives: This article draws from two separate studies combining qualitative and photographic methods to illustrate the unique insights that visual research with smokers can generate for tobacco control. Methods: A purposeful selection of photographs and captions produced by research participants in a study with (1) 20 new fathers that smoke and, (2) a study with 21 adolescent girls that smoke are analysed and discussed in detail. Results: Images produced by smokers illustrate the roles of gender and social context in shaping smoking status, as well as the private struggles with tobacco use experienced by smokers in their day-to-day lives and relationships. Conclusions: Photographic methods have the potential to generate information that may assist in developing tobacco control messaging and programming that speaks to smokers' perceptions of their tobacco use.